2022
DOI: 10.3390/ijerph191811261
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Socioeconomic Factors Influencing the Body Mass Composition of School-Age Children

Abstract: The purpose of the study was to evaluate the components of overweight, obesity, and body mass components among children aged 7 to 13 years against important sociodemographic factors. The analyses considered 315 school-age children from 7 to 13 years of age (164 boys and 151 girls). Each subject was assessed for body weight and height, body weight category, and main sociodemographic factors. Body mass components of body mass (body-fat percentage (BFP), muscle tissue, fat-free mass (FFM), and total body water (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A study by Baran et al ( 50 ) among school-aged children showed a tendency of increased BMI in subjects living outside the city. This was due to a lack of health-related knowledge, limited access to good-quality food, and the limited availability of leisure activities in smaller towns.…”
Section: Discussionmentioning
confidence: 94%
“…A study by Baran et al ( 50 ) among school-aged children showed a tendency of increased BMI in subjects living outside the city. This was due to a lack of health-related knowledge, limited access to good-quality food, and the limited availability of leisure activities in smaller towns.…”
Section: Discussionmentioning
confidence: 94%